P4 4 Ceresian Spin Station - McCrea, Alec; Fotedar, Ayush; Owusu Boamah, Jeremy (Physics Special Topics, 2024)
This paper investigates the feasibility of creating a station on Ceres, as seen in the book series ‘The Expanse’. We calculate the required kinetic energy change of 2.4e+26 J to achieve a spin gravity of 0.3g on the surface of the dwarf planet, and explore how an advanced civilization might acquire such energy, along with the associated complications.